The Repositioning of the Islamic Boarding School Cultural Da'wah Movement in Spreading Wasathiyah Islamic Values - Arif, Arifuddin M.; Cikka, Hairuddin; Zaifullah, Z.; Kahar, M. Iksan (Manunggal Halim Jaya, 2022)
Pondok Pesantren As an indigenous institution engaged in education, it is a center for the effective spread of Islam in Indonesia. The performance of the Islamic boarding school da'wah movement in its socio-historical setting has enforced and maintained the values ​​of the Islamic tradition of Ahlussunnah wa al-jama'ah typical of Indonesia (Islam Nusantara). Its contribution is very large in enlightening the religious understanding of Muslims with its cultural strategies and approaches. As a religious and moral strengthening institution that exists and has a dialectic with the times, it must continue to adapt and reposition its educational and da'wah movement in accordance with the development trends of modern society and the challenges of globalization that have given rise to various configurations, including; advances in science and technology, communication technology, freedom to access knowledge and information, liberal, radical, intolerant attitudes and thoughts, and so on. The configuration of globalization above is an opportunity as well as a challenge for the Islamic boarding school da'wah movement in upholding Wasathiyah Islamic values ​​in Muslim society and the world. The Islamic boarding school da'wah movement must transform from a